The role of the regional milieu for the decision to start a new firm: Empirical evidence for Germany - Rolf Sternberg; Joachim Wagner (European Regional Science Association (ERSA), 2002)
Although comprehensive data from official statistics on new firm formation and entrepreneurs starting a new business are lacking in Germany, we know from empirical studies that entry rates differ between regions, and that the propensity to become an entrepreneur is influenced by socio-demographic variables like sex and age. The focus of our paper is on the link of these two stylised facts. Our econometric study is based on data for 10.000 persons from a recent representative survey of the population in ten German planning regions. We use a version of the probit model that takes care of the regional stratification of the data, and the results of the nonlinear models are carefully interpreted and illustrated. We show that the region matters for the decision to start a new business ceteris paribus, i.e. after controlling for sex, age, education etc.. In a second step we peek inside the black box of the regional effect by showing that the regional level of current start-up activity has a positive ceteris paribus effect on the propensity to become an entrepreneur, while the share of self-employed in the region does not matter. The consequences of these findings for regional policies to encourage new firm entry are discussed briefly in the concluding section.
Keywords: 330